Peran Koperasi Mina Sejahtera Dalam Meningkatkan Kesejahteraan Nelayan Desa Muara - Anjar Supahmi; Syamsuddin RS (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to analyze the role of the Mina Sejahtera Cooperative in improving the welfare of fishers in Muara Village, specifically the discussion is directed at discussing the program, implementation and results of the program. The method used is descriptive with a qualitative approach to describe the conditions and situations or various social reality phenomena in society, which is the object of research. The data collection technique was done using observation, interview and documentation. The results showed that the Mina Sejahtera Cooperative program was based on problems that were often experienced; the program was business capital loans, fishermen savings, social funds, and famine funds. The programs that have been implemented have given good results, namely that the community can have a place and business capital through the programs provided. During times of famine, there is no longer confusion.